Graphene-coated D-shaped terahertz fiber modulator - Wang, Shaona; Su, Mengya; Tang, Longhuang; Li, Xianguo; Li, Xiuyan; Bai, Hua; Niu, Pingjuan; Shi, Jia; Yao, Jianquan (Frontiers in Physics, 2023)
Terahertz (THz) fiber is of interest due to low loss and easy beam shaping. Graphene plays an important role in modulating optical signal. In this paper, a graphene-coated D-shaped THz fiber modulator is proposed. The performance of the proposed modulator is investigated by the finite element method. The inference of geometric parameters of the structure on the proposed modulator is also analyzed and the optimal structure is obtained. The simulation results show that the confinement loss and the full width at half-maximum (FWHM) can be tuned by adjusting the Fermi level of graphene. The proposed THz fiber modulator has potential in future THz fiber communications.